Round, just-below, or precise prices? Cultural differences in the prevalence of price endings in E-commerce - Ventura, Alfio; Troll, Eve Sarah; Soliman, Meikel; Loschelder, David D. (Frontiers in Behavioral Economics, 2025)
IntroductionThe consumer literature distinguishes between three different price endings: round (e.g., 10.00), just-below (e.g., 9.99), and precise (e.g., 9.87) prices. Extant research suggests that these prices can differ markedly in their prevalence between countries. Despite some empirical indication, the link between cultural characteristics and price-ending prevalence has yet to be quantified systematically; we know surprisingly little about why sellers and retailers prefer certain price endings over others.MethodIn the present, pre-registered research (OSF project1), we build on Hofstede's cultural model (1984) to investigate how the three cultural dimensions individualism, uncertainty avoidance, and long-term orientation can explain whether certain price endings are more (vs. less) prevalent. Using a web scraping approach, we extracted 9,200 prices from 23 different countries from an international online marketplace.ResultsOur results indicate that in countries (1) with higher individualism scores round and precise prices are more prevalent while just-below prices are less prevalent. (2) Higher uncertainty avoidance scores predict a higher prevalence of just-below prices and a lower prevalence of precise prices. Finally, (3) a higher long-term orientation predicts a higher prevalence of round prices and lower prevalence of just-below prices.DiscussionAltogether, our results suggest that Hofstede's cultural dimensions are useful in predicting the prevalence of price endings. The present research disentangles divergent empirical findings on price prevalence and furthers our knowledge on the link between cultural dimensions and price-ending practices. Taking a cultural perspective to understand price-ending prevalence is a fruitful avenue for future research and theorizing, as well as organizations, in particular online marketplaces.